2009
DOI: 10.1007/s10439-009-9838-3
|View full text |Cite
|
Sign up to set email alerts
|

Selection of Dynamic Features Based on Time–Frequency Representations for Heart Murmur Detection from Phonocardiographic Signals

Abstract: This work discusses a method for the selection of dynamic features, based on the calculation of the spectral power through time applied to the detection of systolic murmurs from phonocardiographic recordings. To investigate the dynamic properties of the spectral power during murmurs, several quadratic energy distributions have been studied, namely Wigner-Ville, Choi-Williams, smoothed pseudo Wigner-Ville, exponential, and hyperbolic T-distribution. The classification performance has been compared with that usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 59 publications
0
54
0
Order By: Relevance
“…From frequency domain analysis, FFT statistics, Autoregressive Moving-Average (ARMA) features [1], Melfrequency Ceptral Coefficients (MFCC) features [2], sample entropy [6], music features [1], octave band features [1] etc. were extracted and it comprised a total of 102 features.…”
Section: Feature Extractionmentioning
confidence: 99%
“…From frequency domain analysis, FFT statistics, Autoregressive Moving-Average (ARMA) features [1], Melfrequency Ceptral Coefficients (MFCC) features [2], sample entropy [6], music features [1], octave band features [1] etc. were extracted and it comprised a total of 102 features.…”
Section: Feature Extractionmentioning
confidence: 99%
“…In order to estimate such t-f representations, both parametric and nonparametric estimations are generally employed. Among the most popular nonparametric approaches are: short time fourier transform (STFT), wavelet transform (WT); matching pursuit (MP); Choi-Williams distribution (CWD), Wigner-Ville distribution (WVD) [2,6]; and among the parametric models: time-variant autoregressive models, and adaptive filtering [3,4].…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, a signal decomposition grounded on matching pursuit does not necessarily provide the same number of t-f atoms for each recording, hence the multidimensional reduction arises as an additional issue to handle dynamic features of different lengths. Additionally, two-dimensional timefrequency/scale approaches, such as the t-f distributions (linear or quadratic) or even the Wavelet analysis, have also been widely used in biosignal processing, in particular for EEG [5,10] and PCG [6,11]. In this sense, an approach to create optimized quadratic t-f representations is proposed in [12] by designing kernels that lead to the maximum separability among classes.…”
Section: Introductionmentioning
confidence: 99%
“…Specially, changes in physiological conditions and pathologies may produce significant variations. It has been found that non-stationary conditions give rise to changes in the spectral content of the biosignal (Hassanpour et al, 2004;Quiceno-Manrique et al, 2010;Sepúlveda-Cano et al, 2011;Subasi, 2007;Tarvainen et al, 2009;Tzallas et al, 2008). Therefore, time-frequency (t-f) features have been previously proposed for examining the dynamic properties of the spectral parameters during transient physiological or pathological episodes.…”
Section: Introductionmentioning
confidence: 99%
“…Time-frequency dynamic features (TFDF) based on spectral sub-band methods, summarize t-f information in a compact fashion. TFDF set has also demonstrated its capability for discriminating between normal and pathological patterns (Quiceno-Manrique et al, 2010;Sepúlveda-Cano et al, 2011). In this sense, the TFDF set can be suitably estimated by filter bank methods, such as sub-band spectral centroid, sub-band spectral centroid energy, linear cepstral coefficients, or discrete wavelet transform.…”
Section: Introductionmentioning
confidence: 99%